RETRACTED: A mathematical model of the operation process of a radio communication network based on IP technologies in the conditions of information impact during the transmission of a non-repetitive data stream - Khalikov Abdulxak; Khurramov Asliddin; Urokov Olim; Rizakulov Sherzod (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001